The Determination of the “Origin” of Products in South African and SADC Law - C. Vinti (BRICS Law Journal)
This article analyses the landmark case of Commissioner: SARS v. Levi Strauss SA (Pty) Ltd (hereinafter Levi), in which the Supreme Court of Appeal in South Africa decided on the issue of the “origin” of goods in international trade. In South Africa, this issue is regulated by the Customs and Excise Act 91 of 1964 (CEA). The origin of a product is easy to establish when a product is wholly produced in one country. But when the production of a good occurs across different countries, then the rule usually is that the origin of goods is determined based on the “last substantial transformation” of the product. However, in the Levi ruling, the court made this decision without any consideration of South Africa’s international obligations under the Agreement on Rules of Origin and misinterpreted the origin test set out in the Protocol on Trade in the South African Development Community. Moreover, the court also failed to adequately contextualise its reasoning in relation to the default position on the determination of origin in South African law under the CEA. This paper critiques the court’s approach in this regard and assesses its broader implications for origin determinations.